2019
DOI: 10.20945/2359-3997000000120
|View full text |Cite
|
Sign up to set email alerts
|

Association between BRAF (V600E) mutation and clinicopathological features of papillary thyroid carcinoma: a Brazilian single-centre case series

Abstract: Objectives: We aimed to investigate the prevalence of the BRAF (V600E) mutation in consecutive cases of papillary thyroid carcinoma (PTC) in patients diagnosed and treated at the Hospital Sao Rafael (Salvador, BA, Brazil) and evaluate its association with clinical and pathological characteristics of PTC. Subjects and methods: We retrospectively enrolled in the study a total of 43 consecutive PTC patients who underwent total thyroidectomy. We performed DNA extraction from formalinfixed paraffin-embedded (FFPE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
2
15
2
1
Order By: Relevance
“…No correlation was found between BRAF-V600E mutations and the clinicopathological features, including age, gender, LNM, bilateral involvement, vascular tumor thrombus, capsule invasion, foci number, nerve invasion or maximum tumor diameter, while BRAF-V600E expression was signi cantly correlated only with intralobular dissemination in this study (P < 0.05). Our nding was not consistent with that of the study by Pessoa, which demonstrated the independent correlation of BRAF-V600E with age and HT 13 .…”
Section: Discussioncontrasting
confidence: 99%
“…No correlation was found between BRAF-V600E mutations and the clinicopathological features, including age, gender, LNM, bilateral involvement, vascular tumor thrombus, capsule invasion, foci number, nerve invasion or maximum tumor diameter, while BRAF-V600E expression was signi cantly correlated only with intralobular dissemination in this study (P < 0.05). Our nding was not consistent with that of the study by Pessoa, which demonstrated the independent correlation of BRAF-V600E with age and HT 13 .…”
Section: Discussioncontrasting
confidence: 99%
“…We also have shown a significantly higher frequency of BRAF V600E mutation in patients with ages younger than 55 years. Other studies [43][44][45] have shown a higher frequency BRAF V600E mutation among patients with ages higher than 55 years. We believe that this difference in the age pattern of BRAF V600E mutation is mainly due to the differences in patients samples between ours and these studies; as most of our PTC samples (70%) are from patients with ages younger than 55 years (Fig 2).…”
Section: Plos Onementioning
confidence: 85%
“…So far, we have only seen one case reported regarding BRAF mutation (c.1799 T>A;1801_1812del) in primary SCC of the thyroid (27). As we know that BRAF mutations, especially, BRAF V600E mutation is the most common molecular genetic change in PTC (28)(29)(30)(31)(32). Therefore, we believe that the SCC in the metastatic foci of this case may be evolved from the tall-cell subtype of PTC.…”
Section: Discussionmentioning
confidence: 75%